Place attachment in relation to urban street vitality - Zaidin, Nurbazliah; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Mohd Shahli, FitryNadia (Tuengr.com, 2016)
Preliminary studies have highlighted on the importance of the street as public space that provide setting for activities and amenities allowing people to do their activities. However, roles of urban street as public space have weakened due to rapid growth development. It is more focused on the transportation compared to the people, making people feel less attached to the street. Therefore, this paper is aimed to review on the place attachment and its significance in affecting the urban street vitality. The analyzed review comprising on the urban streets in the context of interrelation between behavioral pattern of people and the physical features of streets. These create an attachment feeling in the area that will lead to the vitality of urban streets. Hence, this paper will give an understanding of how place attachment influence people’s presence on the streets in order to attract people and enliven the urban street.